Enhancement of power conversion efficiency in solution processed organic photovoltaic devices by embedded plasmonic gold-silica core-shell nanorods - Wong, Terence Kin Shun (2014)
Chemically synthesized gold-silica nanorods were incorporated into the active layer of solution processed organic photovoltaic devices to enhance the absorption of light by the surface plasmon resonance effect in metallic nanoparticles. Solution processed polymer:fullerene and small molecule:fullerene bulk heterojunction devices were studied. The polymer donors include regioregular poly(3-hexylthiophene) (P3HT) and low bandgap poly[2,6-(4,4-bis-(2-ethylhexyl)- 4N-cyclopenta[2,1-b:3,4-b’] dithiophene)-alt-4,7-(2,1,3-benzothiadiazole)] (PCPDTBT). For the small molecule device, 7,7'-(4,4-bis(2-ethylhexyl)-4H-silolo[3,2-b:4,5-b']-dithiophene-2,6-diyl)bis(6-fluoro-4-(5'-hexyl-[2,2'-bithiophen]-5-yl) benzo[c][1,2,5]thiadiazole) (p-DTS(FBTTh2)2) was used as the donor. The donors are blended with either [6,6]-phenyl- C61-butyric acid methyl ester (PC60BM) or [6,6]-phenyl-C71-butyric acid methyl ester (PC70BM). The gold-silica nanorods have an aspect ratio (length/diameter) of 3.2 and 2.3 and a shell thickness of ~10 nm. Prior to spin coating, the nanorods were added directly to the donor:acceptor blend solution in either chlorobenzene or dichlorobenzene at different weight percentage of the total donor:acceptor weight. The transverse and longitudinal surface plasmon resonance peaks of the gold-slica nanorods overlap with the absorption spectra of all three donor:acceptor blends to differing degrees. As a result, the power conversion efficiency of optimized plasmonic P3HT:PC60BM and PCPDTBT:PC70BM devices with conventional structure under AM1.5G illumination at 100mW/cm2 were increased by 9.3% (to 3.42%) and 20.8% (to 4.11%) respectively relative to the control device without nanorods. For the p-DTS(FBTTh2)2:PC70BM device, the relative improvement as compared to the control device was 24.2% (to 8.01%).